A Comprehensive Overview of Small, Medium, and Micro Enterprise Development in South Africa - Vacu-Ngqila, Nomfundo P.; Ho, Sin-Yu (Acta Universitatis Danubius. Œconomica, 2023)
The small, medium, and mirco enterprise (SMME) sector is viewed as a catalyst for economic growth in the whole world due to its potential to substantially contribute towards employment creation and poverty reduction, among other things. In South Africa (SA), SMMEs have accounted for approximately 40% of gross domestic product and 47% of the workforce in the past few years. Despite the critical role of this sector in SA’s economic growth, literature on understanding its development and trends is scant. This study, therefore, provides a comprehensive analysis on the development of SMMEs in SA. We first conceptualize the term by comparing the definitions of SMMEs from various countries. We later trace the regulatory development of SMMEs during the period from 1940 to 2020. We provide an in-depth discussion on the performance of SMMEs during the period from 2008 to 2021 from different lenses such as provincial, sectoral, and demographic analyses. The results confirmed that, in terms of the number of firms, the sector has remained resilient over the reviewed period. We found that the sector contributes significantly towards economic growth and employment in SA, and this has increased over the years under review. Lastly, we identified several financial and non-financial challenges faced by SMMEs.